Metabolism-Related Signature Analysis Uncovers the Prognostic and Immunotherapeutic Characteristics of Renal Cell Carcinoma - Zhang, Jianye; Zhang, Qi; Shi, Yue; Wang, Ping; Gong, Yanqing; He, Shiming; Li, Zhihua; Feng, Ninghan; Wang, Yang; Jiang, Peng; Ci, Weimin; Li, Xuesong; et al. (Frontiers in Molecular Biosciences, 2022)
Renal cell carcinoma (RCC) is one of the most common urological cancers. RCC has a poor prognosis and is considered a metabolic disease. It has been reported that many metabolic pathways are associated with the development of RCC. However, the prognostic value of metabolism-related genes in RCC is unclear. We herein aimed to establish a scoring system based on the gene expression profile of metabolic genes to evaluate the response to immunotherapy and predict the prognosis of RCC. In this study, we collected multicentre RCC data and performed integrated analysis to characterize the role of tumour metabolism in RCC and explore the relationship between metabolism and prognosis and immune therapy. Based on transcriptomic data, metabolism-related genes were used for nonnegative matrix factorization clustering. We obtained three subclasses of RCC (M1, M2, and M3), and they are associated with different prognoses and immune infiltrate levels. Then, based on the pathway activity of 113 metabolism-related gene signatures, we classified patients into three distinct metabolism-related signatures. Finally, we provide a metabolism-related pathway score (MRPScore) that is significantly associated with RCC prognosis and the response to immunotherapy. Taken together, in this study, we established an RCC classification system based on metabolic gene expression profiles that could further the understanding of the diversity of RCC. We also present the MRPScore, which may be used as an indicator to predict the response to clinical immune therapy.